Electrochromism of Electropolymerized Phthalocyanine-Tetrahydroquinoline Dyads - KOCA, ATIF (ELECTROCHEMICAL SOC INC, 2014)
Electrochromic responses of metallophthalocyanines (MPcs) bearing redox active and electropolymerizable substituents were investigated. Excellent electrochromic responses were observed for metal-free and nickel phthalocyanines bearing electropolymerizable tetrahydroquinoline moieties (Phthalocyanine bearing 2,2,4,7-tetramethyl-3,4-dihydroquinoline, (THQ)) dyads; H2Pc-THQD and NiPc-DHQD). Although MPcs were not electropolymerizable complexes, they were easily electropolymerized on the working electrode after substituting with DHQ moieties. In order to investigate electrochromic features of the complexes, electrochemical and in-situ spectrochronocoulometric analyses of H2Pc-THQD and NiPc-THQD were first of all performed in solution and in solid states as their electropolymerized films to derive their possible usage as electrochromic materials. While both complexes gave common Pc ring based reduction reactions, they were coated on the working electrode with electropolymerization during oxidation reactions. Presence of THQ substituents caused electropolymerization of the complexes during the oxidation reactions. Then in order to examine their possible usages in the electrochromic application fields, phthalocyanine based composite electrodes were prepared with oxidative electropolymerization reactions. Finally their electrochromic features were investigated in different electrolyte systems. Electrochromic measurements showed that the electrodes modified with the electropolymerized films of H2Pc-THQD and NiPc-DHQD enhanced electrochromic properties to MPcs considerably. H2Pc-THQD and NiPc-THQD complexes illustrated excellent electrochromic parameters with high optical contrast, reasonable optical and columbic stabilities, and short response times. (C) 2014 The Electrochemical Society. All rights reserved.
Keywords: THIN-FILMS; METAL-FREE; SPECTROELECTROCHEMICAL PROPERTIES; REVERSIBLE ELECTROCHROMISM; PHOTODYNAMIC THERAPY; COMPLEXES; REDUCTION; COBALT; METALLOPHTHALOCYANINES; PHOTOSENSITIZERS